Activities of Acalypha indica Linn (Euphorbiaceae): A Concise Review of its Phytochemical Components and Ethnomedicinal Uses - G. O., Ojediran; Ojediran, O.; Titilawo, O.Y; Shehu, Z.; Titilawo M.A., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
Acalypha indica Linn belonging to Euphorbiaceae family is used practically as a herbal medicine by the Europe, American, Asian, Africa and other continents. The extracts of the plant has been reported to contain many a chemical constituent with potential activities such as epilepsy, anti-cancer, emetic, anti-bacterial, parasiticide, cough, anthelmintic, analgesic, haemorrhoid, anti-diabetic, anti-oxidant, fungal infection, anti-venom, anti-viral and wound healing activity, it is also known as a rich spring of glycosides, flavonoids and tannins. The principal aim of this review study was to explore the activities of Acalypha indica Linn with a special emphasis on its chemical components and ethnomedicinal uses. Data on this study were assembled from electronic books, Google Scholar, PubMed, Science Direct and Research entryway. By bringing together these facts, we concisely reviewed about the medicinal properties and therapeutic activities establish its importance as a valuable medicinal plant.